Using Ethical Dilemmas to Predict Antisocial Choices with Real Payoff Consequences: An Experimental Study - David L. Dickinson; David Masclet (Institute of Labor Economics (IZA), 2018)
Anti-social behaviours are costly to organizations, and the ability to identify predictors of such behaviours can be valuable. In this paper, we used a within-subjects laboratory design to study choices in the well-known (hypothetical) Trolley problem as well as in a real payoff money-burning experiment that can inform our understanding of moral preferences and antisocial behavior. Choices in both environments respond to incentives (i.e., the relative price of the ethical decision). Trolley problem decisions are consistent with previously known results – individuals prefer no action over action, and they prefer to avoid direct over indirect responsibility when negative consequences would be similar in either instance. In analyzing the determinants of anti-social money burning, our data identify money burning due to inequality aversion, but we also find evidence of pure nastiness (burning money of others to increase one's advantageous inequality). Importantly, we find that willingness to commit ethically dubious acts in the Trolley problem significantly predicts money burning and, more specifically, nastiness. We conclude that choices in hypothetical environments can predict consequential and inefficient antisocial behaviours. Also, utilitarian behaviour in the Trolley dilemma is not linked to antisocial money burning, which contrasts with conclusions in the literature.
Keywords: C90; C91; Z10; 330; experiments; money burning; ethical dilemmas; anti-social behavior; trolley problem